Upaya Pengingkatan Literasi, Numerasi dan Adaptasi Teknologi di SMPN 39 Bengkulu Utara - Annisa Ekavia; Dian Susyla; Ririn Putri Ananda (Gapenas Publisher, 2022)
The Independent Learning Campus Teaching Program (MBKM) organized by the Ministry of Education and Culture. The Teaching Campus Program is currently the third batch assigned to teach in accordance with Literacy and Numeracy guidelines, assist with technology adaptation, and assist school administration and teachers. One of the schools that houses the Teaching Campus is SMP Negeri 39 North Bengkulu which is located in Batik Nau, Batik Nau District, North Bengkulu Regency, Bengkulu. Teaching Campus students also have a responsibility in correcting students' low behavior and interest in learning. The results of this Teaching Campus program are as a process in adding relationships, adding experience outside the world of lectures, developing insight, character and soft skills of students, encouraging and spurring national development by fostering community motivation to participate in development, as well as increasing the role and real contribution of universities and students in national development